Fundamental biochemistry of the early N-glycosylation pathway - Eddershaw, A (2024)
Oligosaccharides destined for use as N-linked glycans are synthesised on phosphorylated dolichols in the endoplasmic reticulum (ER) by a series of glycosyltransferase enzymes known as ALG proteins. Mutations in any of these synthesis enzymes can lead to severe, multisystem syndromes known as congenital disorders of glycosylation (CDG). To date, a number of these glycosyltransferases remain uncharacterised, with most work focussing on yeast homologs. This has been due to the difficulty of accessing either the membrane-associated enzymes or their lipid-based substrates. By combining techniques in biochemistry, molecular biology and synthetic chemistry we aimed to elucidate the mechanisms and kinetics of key glycosyltransferase proteins in the pathway, utilising a library of polyisoprenol probes. The enzymes DPAGT1 (ALG7) and ALG13/ALG14 perform the first phase of early N-glycosylation to yield dolichol pyrophosphate chitobiose on the cytoplasmic leaflet of the ER. Using a baculovirus expression system in insect cells, we present evidence that the human proteins form a multi-enzyme complex that together catalyse this initial step of lipid-linked oligosaccharide synthesis. The kinetics of these enzymes were assessed both when alone and in complex using two experimental formats which has allowed insight into the control and dynamics at the start of the pathway. Iterative attempts were made at structural elucidation by cryoEM of the complex in its unbound and lipid acceptor bound state. Furthermore, we showed that DPAGT1 is highly selective for native dolichol lipids over those typically used in bacterial membranes, whereas ALG13/ALG14 can utilise lipid acceptor substrates of all saturation states. Finally, study of CDG patient mutants helped to inform function of these key enzymes and their pathogenic mechanism. Together, this work aids our understanding on an essential and highly conserved process.